Cathode for electrolytic manganese dioxide production
By using a copper-coated cathode, the issue of cathode deterioration in the production of electrolytic manganese dioxide is addressed, resulting in improved stability and efficiency of the electrolysis process.
Patent Information
- Application Number
- JP2020214249
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-26
- Filing Date
- 2020-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-12-23
AI Technical Summary
The production of electrolytic manganese dioxide is hindered by cathode deterioration when graphite is used, leading to reduced efficiency in the electrolysis process.
A cathode coated with a copper film along its surface shape is used, which suppresses cathode deterioration and maintains stable performance over a long period, enhancing durability and production efficiency.
The copper-coated cathode effectively prevents degradation and maintains low electrolytic voltage, ensuring stable and efficient production of electrolytic manganese dioxide.
Smart Images

Figure 0007661695000004 
Figure 0007661695000005 
Figure 0007661695000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a cathode for producing electrolytic manganese dioxide, and more particularly to a cathode used in the production of electrolytic manganese dioxide to be used as a positive electrode active material in, for example, manganese dry batteries, particularly alkaline manganese dry batteries. [Background technology]
[0002] Electrolytic manganese dioxide is known as a positive electrode active material for manganese dry batteries, particularly alkaline manganese dry batteries, and has the advantages of being excellent in storage stability and inexpensive. In particular, alkaline manganese dry batteries using electrolytic manganese dioxide as a positive electrode active material have excellent discharge characteristics over a wide range of discharge rates, from low-rate discharge to high-rate discharge, and are therefore widely used in electronic devices, portable players, portable information devices, and even game consoles and toys, and demand for them is growing not only in Japan but also around the world.
[0003] Electrolytic manganese dioxide is generally produced by electrolytic oxidation and deposition on the anode by passing a current between the anode and the cathode in a manganese sulfate electrolyte that is acidic with sulfuric acid. Generally, titanium is used for the anode, and graphite is mainly used for the counter electrode, the cathode, although copper and steel are used as rare examples (Patent Document 1).
[0004] When producing electrolytic manganese dioxide, the temperature of the electrolyte must be kept at a high temperature of 93°C to 98°C. Since the electrolysis period is as long as 1 to 4 weeks, a layer of oil with a high boiling point, such as paraffin, is floated on top of the electrolyte as a measure to prevent the electrolyte from evaporating.
[0005] This paraffin adheres to and is absorbed into the electrolytic manganese dioxide deposit not only during electrolysis, but also when the anode on which electrolytic manganese dioxide is deposited is removed from the electrolytic cell after electrolysis is completed and passes through the paraffin oil layer, affecting the product quality of electrolytic manganese dioxide. Therefore, electrolysis methods that remove the paraffin absorbed into the electrolytic manganese dioxide by washing with hot water or that incorporate measures to minimize the incorporation of paraffin are being investigated (Patent Document 2).
[0006] On the other hand, unlike the anode where the electrolytic manganese dioxide precipitation reaction takes place, the cathode where the hydrogen evolution reaction takes place does not have a direct impact on product quality, so it has not received much attention and there have been few cases in which it has been studied in the past.
[0007] However, our investigations have revealed that when graphite is used for the cathode, the cathode deteriorates, resulting in a significant decrease in the production efficiency of electrolytic manganese dioxide. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] WO2000 / 037714 publication [Patent Document 2] JP 2001-247987 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a cathode modified for electrolytic manganese dioxide production, which is coated with a copper film conforming to the cathode surface shape, and a method for producing the same. [Means for solving the problem]
[0010] The present inventors investigated the performance expression and deterioration behavior of cathodes used in electrolytic manganese dioxide production, and conducted intensive research into cathode modification, and as a result, discovered that by using a cathode coated with a copper film conforming to the cathode surface shape, not only is the deterioration of the cathode suppressed, but the performance can be stably maintained over a long period of time and the cathode has excellent durability, which led to the completion of the present invention. That is, the present invention is a cathode for electrolytic manganese dioxide production composed of a graphite plate coated with a copper film.
[0011] The present invention will be described in detail below.
[0012] The cathode for producing electrolytic manganese dioxide of the present invention is composed of a graphite plate covered with a copper film.
[0013] Graphite plates are mostly in the form of plates used in metal refining and plating, but are not limited to this form in nature. As mentioned above, if paraffin is contained inside the graphite plate, it is desirable to remove most of the paraffin by washing with hot water, treating with an organic solvent, degreasing with an alkaline solution, or burning, and it is desirable that paraffin is not present at least near the surface that will be coated with the copper film later. In industry, degreasing cleaners mainly composed of alkaline components may be used.
[0014] The copper coating is a copper-based metal and there is no restriction on its purity, but it preferably contains 60 wt% or more copper, and may be a composite coating with transition metals such as iron and nickel, or non-metals such as sulfur and phosphorus.
[0015] The copper film acts as an electrode catalyst by being on the graphite plate and maintaining electrical contact with it. The hydrogen evolution electrode catalytic activity of copper is known to be superior to that of carbon, the material from which graphite is made, even in terms of basic chemistry (Urevans, The Corrosion and Oxidation of Metals). For example, the hydrogen overvoltage of carbon is 0.7 V, while that of copper is 0.53 V, and it is said to show superior activity at low hydrogen overvoltages.
[0016] The thickness of the copper coating coated on the graphite plate surface is not limited, but is preferably 0.3 μm to 100 μm, more preferably 0.5 μm to 100 μm, even more preferably 0.5 μm to 50 μm, and most preferably 1 μm to 20 μm. The graphite plate surface may have irregularities of several μm to several mm, and it is desirable that the irregularities on the graphite plate surface are entirely covered with a copper coating having the above-mentioned thickness, but it is not necessarily required to be completely covered, and the coverage may be at least such that copper can exhibit electrocatalytic activity, for example, a coverage of 40%. Note that the parts of the graphite plate that are not immersed in the electrolyte, such as the power supply part that supplies current to the graphite plate, do not contribute to the electrocatalytic reaction, and therefore do not necessarily need to be covered with a copper coating.
[0017] The cathode for producing electrolytic manganese dioxide of the present invention can be produced by using a graphite plate as a working electrode and coating it with a copper film by electroplating or electroless plating in an electrolyte containing copper ions.
[0018] Methods for coating the graphite plate with a copper film include, for example, electroplating and electroless plating.
[0019] In the electroplating method, a graphite plate is immersed in an electrolyte containing copper ions, and a current is passed between the graphite plate and a counter electrode (anode) for a predetermined period of time to coat the graphite plate with copper.
[0020] The electrolyte containing copper ions is prepared by dissolving copper salts such as copper sulfate, copper hydrochloride, copper nitrate, and copper pyrophosphate in the electrolyte. In addition to the copper salt, the electrolyte may contain additives such as complexing agents such as citrate ions, tartrate ions, phosphate ions, and pyrophosphate ions, or gloss agents such as dextrin and lauryl sulfate ions, or sulfur-containing substances such as thiourea. In addition, the electrolyte containing copper ions may be mixed with transition metal ions such as iron ions and nickel ions as other metal ions to obtain a copper-based alloy coating. However, there is no problem if the electrolyte contains metal ions such as manganese ions that do not directly interact with copper ions and do not precipitate on the graphite plate.
[0021] The pH of the electrolyte may be adjusted depending on the additives and properties of the metal ions contained in the electrolyte, but in the present invention, it is generally pH 0.1 or more and pH 7 or less.
[0022] The copper ion concentration of the electrolyte is not particularly limited, but may be, for example, 10 mg / L or more and 30 g / L or less. The electrolyte temperature is also not limited, but may be, for example, 40° C. or more and 98° C. or less.
[0023] For the counter electrode (anode), insoluble precious metals such as platinum and iridium are mainly used, but by controlling the concentration of components in the electrolyte, even metals that undergo electrolytic dissolution, such as copper, can be used.
[0024] The current density of the graphite plate during electrolysis was 20 A / m 2 More than 1000A / m 2 The time is selected within the following range, and electrolysis is continued until the desired copper coating thickness is achieved.
[0025] In the electroless plating method, a reducing agent is added to an electrolyte containing copper ions, and a pretreated graphite plate is immersed in the electrolyte for a predetermined period of time to be coated with copper.
[0026] The electrolyte containing copper ions is prepared by dissolving copper salts such as copper sulfate, copper hydrochloride, copper nitrate, and copper pyrophosphate in the electrolyte. In addition to the copper salt, the electrolyte may contain additives such as complexing agents such as citrate ions, tartrate ions, phosphate ions, and pyrophosphate ions, polyacetylene glycol surfactants, sulfur-containing substances such as thiourea, and boric acid. In addition, the electrolyte containing copper ions may be mixed with transition metal ions such as nickel ions as other metal ions to obtain a copper-based alloy coating.
[0027] As the reducing agent, sodium hypophosphite is typically used.
[0028] The pH of the electrolyte is adjusted according to the properties of the additives and metal ions contained in the electrolyte, but in the case of the present invention, it is adjusted to be generally pH 7 or more and pH 12 or less.
[0029] The copper ion concentration of the electrolyte is not particularly limited, but may be, for example, 0.5 g / L or more and 30 g / L or less. The electrolyte temperature is also not limited, but may be, for example, 20° C. or more and 80° C. or less.
[0030] Bath load in electroless plating (volume of electrolyte V(m 3 ) to the area A (m 2 The V / A ratio of the immersion temperature is selected from the range of about 5 to 30, and the immersion is continued until the desired copper coating thickness is achieved.
[0031] Pretreatment of graphite plates may involve washing with hot water, treatment with organic solvents, degreasing treatment using an alkaline solution, etc., to remove paraffin from the graphite plate, or plating with another metal as a base for the copper coating in advance. Industrially, degreasing cleaners mainly composed of alkaline components may be used to remove paraffin from the graphite plate. Effect of the Invention
[0032] The cathode for producing electrolytic manganese dioxide of the present invention suppresses deterioration of the cathode and enables the electrolysis voltage to be maintained low, and therefore allows efficient and stable production efficiency of electrolytic manganese dioxide to be achieved. [Brief description of the drawings]
[0033] [Figure 1] 1 is a photograph showing the appearance of the cathode obtained in Comparative Example 3. [Diagram 2] 1 is a photograph showing the appearance of the cathode obtained in Example 1. [Diagram 3] 2 is a cross-sectional photograph of the surface vicinity of the cathode obtained in Example 1. [Figure 4] 1 is a photograph showing the appearance of the cathode obtained in Example 3. [Diagram 5] 1 is a photograph showing the appearance of the cathode obtained in Example 4. [Figure 6] 1 is a photograph showing the appearance of the cathode obtained in Example 7. [Figure 7] 1 is a photograph showing the appearance of the cathode obtained in Example 8. [Figure 8] 1 is a photograph showing the appearance of the cathode obtained in Example 9. [Figure 9] 1 is a Tafel plot showing the change in logarithm of current density and potential during hydrogen generation in Examples 1 to 4, 8 and 9, and Comparative Example 4. [Figure 10] 1 is a Tafel plot showing the change in logarithm of current density and potential during hydrogen generation in Comparative Examples 1 and 3 to 6. EXAMPLES
[0034] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0035] <How to prepare a cathode for measuring potential performance> A cathode substrate plate such as graphite was cut to have a 1 cm square surface, so that the measurement direction was the only exposed surface. A nickel lead wire was embedded on the back side and, while maintaining electrical contact, the plate was embedded in hardening resin (Technovit #4071, Maruto). The exposed surface was then polished with #1500 sandpaper to form a cathode (electrode area 1 × 1 cm). 2 ) was prepared.
[0036] When preparing a cathode covered with a copper film, the exposed surface of the cathode was immersed in an electrolyte containing copper ions, and a copper film was formed by electroplating or electroless plating.
[0037] <Measurement of potential performance> The exposed surface of the cathode or the copper-coated cathode was immersed in a 28 g / L sulfuric acid solution at 96°C, and a platinum plate was used as the counter electrode and a saturated calomel electrode (SCE) was used as the reference electrode. The electrodes were connected to a potentiogalvanostat (HA-151B, Hokuto Denko Corporation) and a current of 0.05 to 1 A / dm was applied. 2 The measurement was performed by applying a current of 1000 kcal / L and reading the value of the cathode potential relative to the SCE reference electrode.
[0038] Of these, 0.5A / dm 2 The cathode potential when a current of 0.05 to 1 A / dm was applied was shown as a representative value of the cathode potential for each cathode. 2 The degree of potential change during this period is shown as the Tafel slope (used as an index of the electrochemical hydrogen evolution mechanism of the electrode catalyst material).
[0039] <Electrolytic test method> A mixed solution of sulfuric acid and manganese sulfate was used as the electrolyte, and a manganese sulfate solution with a manganese ion concentration of 46 g / L was continuously supplied to the electrolytic cell. An electric current was applied between the cathode or the copper-coated cathode and the titanium anode, and electrolytic manganese dioxide was deposited on the titanium anode. The electrolytic current density was 0.68 A / dm 2The electrolysis was carried out for 18 days while adjusting the electrolysis temperature to 96° C. and the sulfuric acid concentration in the electrolytic cell to 34 g / L. During the electrolysis, the cathode potential was measured using a mercury / mercury sulfate electrode as a reference electrode.
[0040] Comparative Example 1 A graphite plate (PSG322, manufactured by SEC) impregnated with 24 mg / g of paraffin was used to prepare a cathode, and potential measurements were performed. The cathode potential was -1.02 V vs. SCE, and the Tafel slope was -0.080 V / dec.
[0041] Comparative Example 2 When the graphite plate of Comparative Example 1 was subjected to paraffin extraction and removal treatment with hexane, the amount of remaining paraffin was <0.5 mg / g. A cathode was made from the graphite plate subjected to the paraffin removal treatment, and the potential was measured. The cathode potential was -0.70 V vs. SCE.
[0042] Comparative Example 3 When the graphite plate of Comparative Example 1 was used to remove paraffin by combustion, the amount of remaining paraffin was <0.5 mg / g. A cathode was made from the graphite plate that had been subjected to the paraffin removal treatment, and potential measurements were performed. The cathode potential was -0.62 V vs. SCE, and the Tafel gradient was -0.083 V / dec. A photograph of the appearance of the obtained cathode is shown in Figure 1.
[0043] Example 1 The cathode made of the graphite plate subjected to the paraffin removal treatment of Comparative Example 3 was placed in a copper (Cu 2+ The electrode was immersed in an electrolyte containing 10 g / L of ions and 35 g / L of sulfuric acid, and the counter electrode was a platinum plate. The temperature was kept at 70°C, and the current density was 0.05 A / dm 2 The cathode was electroplated at 400 K for 50 minutes to obtain a cathode. The cathode potential after electroplating was -0.39 V vs. SCE, and the Tafel slope was -0.060 V / dec. Figure 2 shows a photograph of the appearance of the obtained cathode, and Figure 3 shows a cross-sectional photograph of the surface area.
[0044] Examples 2 to 4 A cathode was obtained by electroplating in the same manner as in Example 1, except that the electroplating conditions of the current density and time were changed in Example 1. These electroplating conditions and the cathode potential and Tafel slope values of the cathode after electroplating are shown in Table 1.
[0045] [Table 1]
[0046] A photograph of the appearance of the cathode obtained in Example 3 is shown in FIG. 4, and a photograph of the appearance of the cathode obtained in Example 4 is shown in FIG.
[0047] Example 5 Using a cathode made of a graphite plate that had been subjected to the paraffin removal treatment of Comparative Example 3, copper (Cu) was immersed in an aqueous solution with a manganese ion concentration of 27 g / L and a sulfuric acid concentration of 36 g / L. 2+ The electrode was immersed in an electrolyte prepared by adding 10 mg / L of 1,000 μg ... 2 While maintaining the temperature at 96°C, electricity was passed for 60 minutes to perform electroplating, and a cathode was obtained. During electroplating, hydrogen gas bubbles were observed to be generated from the exposed surface of the cathode, but after electroplating, the exposed surface of the cathode turned copper color, and it was visually confirmed that it was coated with a copper film. The cathode potential of the cathode after electroplating was -0.47V vs.SCE.
[0048] Examples 6 to 7 In Example 5, copper (Cu 2+ Cathode was obtained by electroplating in the same manner as in Example 5, except that the concentration of .OMEGA.) ions was 100 mg / L and 1000 mg / L. In both cases, hydrogen gas bubbles were observed to be generated from the exposed surface of the cathode during electroplating, but after electroplating, the exposed surface of the cathode turned copper color, and it was visually confirmed that it was covered with a copper coating. These electroplating conditions and the cathode potential value of the cathode after electroplating are shown in Table 1. A photograph of the appearance of the cathode obtained in Example 7 is shown in FIG. 6.
[0049] Example 8 The cathode made of the graphite plate subjected to the paraffin removal treatment of Comparative Example 3 was placed in a copper (Cu 2+ ) ions 2g / L, nickel (Ni 2+ The cathode was immersed in an electrolyte solution containing 0.14 g / L of cations, 13.5 g / L of sodium citrate, 29 g / L of sodium hypophosphite monohydrate, 31 g / L of boric acid, and 0.4 g / L of starch under conditions of a bath load (V / A) of 10, pH 9.0, and temperature of 60°C for 30 minutes to obtain a cathode. After electroless plating, the entire immersed part of the cathode turned copper color, and it was visually confirmed that it was coated with a copper film. After removing the copper film with sandpaper except for the exposed surface of the cathode, the cathode potential of the cathode was measured to be -0.46 V vs. SCE, and the Tafel slope was -0.052 V / dec. A photograph of the appearance of the obtained cathode is shown in Figure 7.
[0050] Example 9 A cathode was obtained by electroless plating in the same manner as in Example 8, except that the pH of the electrolytic solution was set to 10.5. As in Example 8, after electroless plating, the entire immersed part of the cathode turned copper color, and it was visually confirmed that it was coated with a copper film. The cathode potential of the cathode measured after removing the copper film with sandpaper, leaving only the exposed surface of the cathode, was -0.47 V vs. SCE, and the Tafel slope was -0.059 V / dec. A photograph of the appearance of the obtained cathode is shown in FIG. 8.
[0051] Comparative Example 4 A cathode was prepared using a copper plate instead of the graphite plate used in Comparative Example 1, and potential measurements were performed. The cathode potential was −0.49 V vs. SCE, and the Tafel slope was −0.062 V / dec.
[0052] Comparative Example 5 A cathode was prepared using a nickel plate instead of the graphite plate used in Comparative Example 1, and potential measurements were performed. The cathode potential was −0.59 V vs. SCE, and the Tafel slope was −0.077 V / dec.
[0053] Comparative Example 6 A cathode was prepared using a platinum plate instead of the graphite plate used in Comparative Example 1, and potential measurements were performed. The cathode potential was −0.35 V vs. SCE, and the Tafel slope was −0.034 V / dec.
[0054] FIG. 9 shows Tafel plots illustrating the changes in logarithm of current density and potential during hydrogen generation for Examples 1 to 4, 8, and 9, and Comparative Example 4, and FIG. 10 shows Tafel plots illustrating the changes in logarithm of current density and potential during hydrogen generation for Comparative Examples 1 and 3 to 6.
[0055] As described above, the cathodic potential was improved by coating a thin copper film on a graphite plate from which paraffin had been removed. The characteristic level was superior to that of copper metal and close to that of platinum precious metal.
[0056] Example 10 A cathode was obtained in the same manner as in Example 8, except that electroless plating was carried out for 60 minutes. The obtained cathode was subjected to an electrolytic test according to the <Electrolytic test method>. The paraffin content of the obtained cathode was <0.5 mg / g, and the copper content was 1.88 mg / cm 2 The thickness of the copper coating was 2.10 μm. The cathode potential of this cathode with respect to the sulfuric acid / mercury sulfate reference electrode was -0.91 V vs. Hg2SO4. These values are shown in Table 2.
[0057] [Table 2]
[0058] Examples 11 to 14 A cathode was obtained in the same manner as in Example 10, except that the electroless plating time, the copper content, and the copper coating thickness were changed. An electrolysis test was performed on the obtained cathode according to the <Electrolysis test method>. The values are summarized in Table 2. In Examples 13 and 14, paraffin was detected in the cathode, and it was presumed that paraffin re-permeated into the graphite substrate during electrolysis.
[0059] Comparative Example 7 An electrolysis test was carried out according to the <Electrolysis Test Method> using the graphite plate that had been subjected to the paraffin removal treatment of Comparative Example 3 as the cathode. The paraffin content of this cathode was <0.5 mg / g. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.35 V vs. Hg2SO4.
[0060] Comparative Example 8 An electrolysis test was carried out using a graphite plate (PSG322, manufactured by SEC) permeated with 54 mg / g of paraffin as the cathode according to the <Electrolysis Test Method>. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.52 V vs. Hg2SO4.
[0061] Comparative Example 9 An electrolysis test was carried out using a copper plate as the cathode according to the <Electrolysis Test Method>. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.08 V vs. Hg2SO4.
[0062] As described above, by coating a thin copper film by electroless copper plating on a graphite plate from which paraffin had been removed by combustion, the cathode potential was improved even in electrolysis for electrolytic manganese dioxide deposition using a sulfuric acid-manganese sulfate electrolyte. The characteristic level was superior to that of copper metal, and good performance was demonstrated even when paraffin re-permeated into the graphite substrate during electrolysis.
[0063] Example 15 A graphite plate (PSG322, manufactured by SEC) permeated with 54 mg / g of paraffin was used, and the plate was immersed in a degreasing cleaner (SC-60, manufactured by Asahi Yushi Chemicals) at 55°C for 15 minutes, washed with water, and then electroless plating was performed for 60 minutes. The cathode thus obtained was subjected to an electrolytic test according to the <Electrolytic Test Method>. The paraffin content of the cathode thus obtained was <0.5 mg / g, and the copper coating thickness was 1.8 μm. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -0.97 V vs. Hg2SO4. These values are shown in Table 3.
[0064] [Table 3]
[0065] Example 16 A graphite plate (PSG322, manufactured by SEC) infiltrated with 54 mg / g of paraffin was used to remove the paraffin by burning, and then electroplating was performed in the same manner as in Example 1 to obtain a cathode. An electrolytic test was performed on the obtained cathode according to the <Electrolytic Test Method>. The paraffin content of the obtained cathode was <0.5 mg / g, and the copper coating thickness was 2.4 μm. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.06 V vs. Hg2SO4. These values are shown in Table 3.
[0066] Example 17 A graphite plate (PSG322, manufactured by SEC) permeated with 54 mg / g of paraffin was immersed in a degreasing cleaner (SC-60, manufactured by Asahi Yushi Chemicals) at 55°C for 15 minutes, washed with water, and electroplated in the same manner as in Example 16 to obtain a cathode. An electrolytic test was performed on the obtained cathode according to the <Electrolytic Test Method>. The paraffin content of the obtained cathode was <0.5 mg / g, and the copper coating thickness was 2.6 μm. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.03 V vs. Hg2SO4. These values are shown in Table 3.
[0067] Example 18 A graphite plate (PSG322, manufactured by SEC) permeated with 54 mg / g of paraffin was electrolytically degreased for 15 minutes with a degreasing cleaner (SC-60, manufactured by Asahi Yushi Chemicals) at 40°C, washed with water, and electroplated in the same manner as in Example 16 to obtain a cathode. An electrolytic test was performed on the obtained cathode according to the <Electrolytic Test Method>. The paraffin content of the obtained cathode was <0.5 mg / g, and the copper coating thickness was 3.0 μm. The cathode potential of this cathode relative to the sulfuric acid / mercury sulfate reference electrode was -1.07 V vs. Hg2SO4. These values are shown in Table 3.
[0068] As described above, by coating a thin copper film by either electroless plating or electroplating on a graphite plate from which part of the paraffin had been removed using a commercially available degreasing agent, the cathode potential was improved in electrolysis for electrolytic manganese dioxide deposition using a sulfuric acid-manganese sulfate electrolyte. The characteristic level was excellent, equivalent to or better than that of copper metal. [Industrial Applicability]
[0069] The present invention has excellent activity of the cathode's hydrogen generation electrode catalytic reaction and can maintain a low electrolysis voltage for a long period of time, making it possible to stably produce electrolytic manganese dioxide at a low power consumption rate. [Explanation of symbols]
[0070] 1 Exposed graphite surface 2 Embedding resin part 3 Exposed graphite surface covered with copper film 4 Embedding resin 5 Copper coating 6. Graphite
Claims
1. A cathode for use in the production of electrolytic manganese dioxide, comprising a graphite plate coated with a copper film.
2. 2. The cathode for producing electrolytic manganese dioxide according to claim 1, wherein the thickness of the copper coating is from 0.3 μm to 100 μm.
3. 3. The cathode for producing electrolytic manganese dioxide according to claim 1, wherein the copper coating is made of a copper-based metal containing 60 wt % or more of copper.
4. 4. The cathode for producing electrolytic manganese dioxide according to claim 1, wherein the copper coating is made of a copper-based metal containing iron or nickel.
5. 5. The cathode for producing electrolytic manganese dioxide according to claim 1, wherein the copper coating is made of a copper-based metal containing phosphorus or sulfur.
6. The cathode for producing electrolytic manganese dioxide according to any one of claims 1 to 5, characterized in that the graphite plate contains paraffin.
7. The method for producing a cathode for producing electrolytic manganese dioxide according to any one of claims 1 to 6, characterized in that a graphite plate is used as a working electrode and a copper coating is formed by electroplating in an electrolyte containing copper ions.
8. The method for producing a cathode for producing electrolytic manganese dioxide according to any one of claims 1 to 6, characterized in that a graphite plate is used as a working electrode and a copper coating is formed by electroless plating in an electrolytic solution containing copper ions.
9. A method for producing a cathode for producing electrolytic manganese dioxide as described in claim 7 or claim 8, characterized in that the copper ion concentration in the copper ion-containing electrolyte is 0.01 g / L or more and 30 g / L or less.
10. A method for producing electrolytic manganese dioxide, comprising using the cathode for producing electrolytic manganese dioxide according to any one of claims 1 to 6.
11. A method for producing a positive electrode material for a battery, the positive electrode material being synthesized using electrolytic manganese dioxide produced by the method for producing electrolytic manganese dioxide according to claim 10.
Citation Information
Patent Citations
Preparation of manganese dioxide
JP1985211086A
Cathode for producing electrolytic manganese dioxide
JP1988062893A
Carbonaceous electrode and production thereof
JP1989306591A
Method for manufacturing electrolytic manganese dioxide
JP2001247987A
Method for manufacturing electrolytic manganese dioxide
JP2002161386A